Conceptual Approaches to Forecast Recruitment Needs at the Regional Level - Simonova, Marina V.; Ilyukhina, Larisa A.; Bogatyreva, Irina V.; Vagin, S. G.; Nikolaeva, K. S. (International Review of Management and Marketing, 2016)
The article deals with the current state of the labor market, which is characterized by such problems as: the structural imbalance of the labor market; lack of skilled workforce; the aging of workforce; youth unemployment; the low rate of productive jobs; employers’ non-compliance with applicants’ qualification. The education system, prevailing in our country and now passing through a systemic and structural adjustment, does not fully comply with the changes in the economy. The existing and currently applied regulation systems of interaction between the labor market and employers cannot adequately meet the needs of our society. One of the possible methods to regulate the labor market, taking into account employers’ needs, the possibilities of the education system, the interests of the population in the regulatory impact of the state, can be a scientifically substantiated recruitment forecast in the long and medium term, which allows you in a balanced manner calculate recruitment requirements of the economy in the strategic and operational mode. The need for recruitment forecasts is usually based on the assumption that the discrepancy between supply and demand does not lead to a restructuring of the labor market. Regulation of recruitment requirements at the regional level is necessary to meet the requirements of the territory economy for skilled labor on the basis of the regional and federal state order to institutions of vocational education. Since there is no a single federal regulatory model of demand and supply for skilled labor, as well as taking into account the diversity of geographical and economic parameters of economic regions in Russia, it is justified to have and implement various models of human resource forecast in the Russian Federation. Using an example of the Samara area the authors suggest calculating multifunctional dependence control on demand and supply for skilled labor on the basis of deterministic or stochastic factor of economic and mathematical models. Application of economic and mathematical modeling can be useful for better understanding of the required structure of labor potential, quantitative parameters of the aggregated qualified and professional groups. Keywords: HR forecast; Labor market; Employers; Balance of the labor market; Employment potential; Education; Field of study; Graduates. JEL Classifications: J40; J48